Relationship between electrical activity and left atrial volume during atrial fibrillation. (19th May 2022) - Adragao, P; Nascimento Matos, D; Costa, FM; Galvao Santos, P; Rodrigues, G; Carmo, J; Salome Carvalho, M; Carmo, P; Cavaco, D; Morgado, F; Mendes, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pulmonary veins (PV) ostia were previously identified as the left atrium (LA) areas with the shortest refractory period during sinus rhythm. Pulmonary veins isolation (PVI) became standard of care, but clinical results are still suboptimal. Currently, atrial fibrillation (AF) cycle length mapping (CLM) is possible due to a special tool of the Carto® electroanatomical mapping, which identifies areas in the left atria with shortest refractory period, during AF. Purpose: Using this new EAM feature, our study aimed to assess the relationship between short refractory period LA areas and left atrial volume and AF type, known predictors of AF relapse. Methods: Retrospective analysis of an unicentric registry of individuals with symptomatic drug-refractory AF who underwent PVI AF ablation with Carto® EAM. CLM was performed. CL maps were created with a high-density mapping Pentaray® catheter before and after PVI. We assessed areas of short cycle length (SCL) (defined as 120 to 250ms), and their relationships with complex fractionated atrial electrograms (CFAE), and low-voltage zones (from 0.1 to 0.3mV). Results: A total of 35 patients (21 men, median age 62 IQR 53-71 years) were included. Most patients presented with persistent AF (n=23, 66%), and 8 patients (23%) had a previous PVI. The mean shortest measured cycle length in AF was 134ms (SD ± 23ms). There was a negative correlation between LA volume and SCL areas after PVI (Spearman Correlation coefficient [ρ] = - 0.47, P = 0.037). There was no correlation between LA volume and SCL areas before the PVI procedure (ρ = -0.06, P = 0.776), nor between AF type and SCL (ρ = -0.118, P = 0.620). All patients presented areas of SCL located in the PVs or their insertion, 76% in the posterior/roof region adjacent to the left superior pulmonary vein (LSPV) and 76% in the anterior region of the wall adjacent to the right superior pulmonary vein (RSPV). These two areas remained the fastest even after PVI. The anterior mitral region rarely presented SCL (16%). SCL were related to low-voltage areas in 93% and were adjacent to CFAE in 84% of the cases. Low-voltage areas and CFAE were more frequent and had a larger LA dispersion than SCL. Conclusion: Our study shows that LA volume, not AF type, is correlated with remaining SCL areas after a pulmonary vein isolation procedure. This finding suggests a possible causal link between increased LA volume and AF relapse post-PVI. More studies are needed to assess the role of the SCL areas as a potential ablation target and their impact on AF ablation outcomes.